Finding the Bad Apples in the Barrel Using the Market Value of Equity to Signal Banking Sector Vulnerabilities - Kerry, Will (IMF Working Papers; Working Paper ;, 2019)
This paper measures the performance of different metrics in assessing banking system vulnerabilities. It finds that metrics based on equity market valuations of bank capital are better than regulatory capital ratios, and other metrics, in spotting banks that failed (bad apples). This paper proposes that these market-based ratios could be used as a surveillance tool to assess vulnerabilities in the banking sector. While the measures may provide a somewhat fuzzy signal, it is better to have a strategy for identifying bad apples, even if sometimes the apples turn out to be fine, than not being able to spot any bad apples before the barrel has been spoiled.